2016
DOI: 10.4103/1742-6413.196239
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected diagnosis of ectopic liver diagnosed by fine needle aspiration

Abstract: The differential diagnosis of perigastric masses is broad, ranging from benign to malignant entities. Among the benign entities, accessory liver lobes and ectopic liver are unusual and often incidentally discovered. Here, we report a patient with malignant melanoma who was clinically suspected to have a perigastric metastasis or a gastrointestinal stromal tumor but was ultimately diagnosed by fine needle aspiration (FNA) to have benign ectopic liver. A 47-year-old male was diagnosed with malignant melanoma of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Currently, the most common site of incidental finding of EL is on the wall of the gallbladder [1,5]. Moreover, EL has also been identified in the thorax, lung, pancreas, umbilicus, adrenals, pylorus, inferior vena cava and within congenital abdominal wall anomalies [2,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most common site of incidental finding of EL is on the wall of the gallbladder [1,5]. Moreover, EL has also been identified in the thorax, lung, pancreas, umbilicus, adrenals, pylorus, inferior vena cava and within congenital abdominal wall anomalies [2,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the intrathoracic ectopic or accessory liver lobes were connected to the orthotopic liver by means of a small pedicle that pierced the diaphragm or passed through a small hiatus (Chen et al). From intra abdominal sites the most frequent site where are found the majority of ectopic livers is the gallbladder (Tejada & Danielson;Arakawa et al;Sakarya et al, 2002;Acar et al, 2002;Catani et al, 2011;Martinez et al;Bal et al, 2015;Yahya et al, 2016;Karaca et al, 2016). Occasionally ectopic liver have been found in other organs like stomach (Huang et al, 2015, Barazza et al, 2016, in the upper pole of the spleen (Zonca et al, 2013), in the ligamentum hepato-umbilicalis (Lara-Díaz et al, 2011;Vaideeswar et al, 2011;Zonca et al), in the pancreas , kidney (Merve & Scheimberg 2014), left adrenal gland (Hashimoto et al, 1997) or have been found as intracaval floating mass (Morris et al, 2012;Rafiei et al, 2012).…”
Section: Case Reportmentioning
confidence: 99%
“…Fine needle aspiration biopsy (FNAB) is a simple, rapid, indicative, and accurate method to diagnose tumours owing to its minimal invasiveness and safety; it allows for the observation of abnormal cytological changes in suspicious lesions . Over the past few years, several studies have confirmed the diagnostic utility of FNAB in cancer, and therefore, it is now widely used in clinical practice . Owing to innovative developments in FNA technology, we can now collect more cells to prepare cell blocks (CB) that can be used for cell smears and immunohistochemistry (IHC) staining analysis, which compensates for some of the shortcomings of simple smears in organisational structure and cell morphology.…”
mentioning
confidence: 99%